Can Crises Affect Citizen Activism? Evidence from a Pandemic - Farzana Afridi; Ahana Basistha; Amrita Dhillon; Danila Serra (Institute of Labor Economics (IZA), 2024)
We consider the largely unexpected shock caused by the second wave of the COVID-19 pandemic in India to assess whether major crises that impact the well-being of a large number of individuals can be catalysts for civic activism. Exploiting state-level variation in COVID-19 peaks and quasi-randomness in subjects' participation in an online survey fielded between March and July 2021, we elicit willingness to act against fraud and corruption in the provision of health services by supporting an NGO engaged in advocacy for health-sector regulation. By comparing responses of subjects surveyed before and after the COVID-19 peak in their state of residence, we find evidence of a large and significant increase in anti-corruption activism post peak. Our data suggest that this surge in activism can be attributed to heightened perceptions of corruption in the healthcare sector, increased awareness of individuals' own rights and entitlements, a greater willingness to take risks, and a positive shift in beliefs regarding others' willingness to fight corruption in the provision of healthcare services.
Keywords: D73; D83; I15; 330; crisis; corruption; health sector; India; COVID-19